2021
DOI: 10.1159/000516772
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Timed Up and Go Assessment in Amyotrophic Lateral Sclerosis: A Pilot Study

Abstract: Progressive loss of walking ability in amyotrophic lateral sclerosis (ALS) has been scarcely studied as a potential predictive factor for survival in motor neuron disease. We aimed to assess the progression of gait decline and its association with mortality in ALS using the Timed Up and Go test (TUG). Patients were followed up prospectively at the Centre for ALS and Related Disorders in Geneva University Hospitals between 2012 and 2016. The TUG was performed at baseline and subsequent evaluations occurred ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(19 reference statements)
1
1
0
Order By: Relevance
“…This relationship demonstrates the benefit of utilizing the full GMS to consider functional mobility such as GV and ambulation. Our findings echo Sukockienė's findings that total ALSFRS-R scores significantly and negatively correlate with the TUG 48) , pALS were slower as their self-rated function decreased. We also found that the TUG score was significantly and negatively correlated with the GMS and its three components.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This relationship demonstrates the benefit of utilizing the full GMS to consider functional mobility such as GV and ambulation. Our findings echo Sukockienė's findings that total ALSFRS-R scores significantly and negatively correlate with the TUG 48) , pALS were slower as their self-rated function decreased. We also found that the TUG score was significantly and negatively correlated with the GMS and its three components.…”
Section: Discussionsupporting
confidence: 90%
“…We concur that in a general population, this outcome measure should not be used in isolation. However, the TUG continues to be used in clinical practice and the activities required for the TUG can add valuable information in the assessment of patient function 48,52,53) . Further investigation of the TUG, including larger studies that assess inter-rater and intra-rater reliability, how the inability to perform the TUG test relates to risk of falls, the influence of using ADs and braces, and the association of TUG scores with quality of life will help better define the role of the TUG test in the clinical care of pALS 27) .…”
Section: Discussionmentioning
confidence: 99%